1999
DOI: 10.1111/j.1574-6941.1999.tb00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for zooplankton-associated nitrogen-fixing anaerobes based on amplification of the nifH gene

Abstract: A fragment of the nifH gene was amplified from anaerobic microbial enrichments initiated with marine planktonic invertebrates, including copepods and euphausids. A number of the nifH sequences from these enrichments were phylogenetically related to Cluster III nifH sequences of Clostridium pasteurianum and Desulfovibrio gigas. nifH fragments were cloned and sequenced from strains of Desulfobacter curvatus, Desulfonema limicola, and Chromatium purpuratum in order to provide the basis for identifying nifH sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…The presence of nifH sequences related to anaerobic microorganisms suggests that anoxic microsites exist in the oxygenated water column. It has been suggested that these bacteria thrive on particles or in association with zooplankton [9], [41], [45], [58]. However, their presence in prefiltered surface samples (Sargasso DNA2; [24], [41]) as well indicates that they may be facultative anaerobes thriving even in the fully oxygenated free-living phase.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of nifH sequences related to anaerobic microorganisms suggests that anoxic microsites exist in the oxygenated water column. It has been suggested that these bacteria thrive on particles or in association with zooplankton [9], [41], [45], [58]. However, their presence in prefiltered surface samples (Sargasso DNA2; [24], [41]) as well indicates that they may be facultative anaerobes thriving even in the fully oxygenated free-living phase.…”
Section: Resultsmentioning
confidence: 99%
“…Potential sources of hydrogen in the ocean photic zone include photochemical reactions [27], algal metabolism [28], and heterotroph activity in anoxic microenvironments [29]. Hydrogenase-like genes are also harbored by the marine plankton Roseobacter clade isolates Roseovarius sp.…”
Section: Resultsmentioning
confidence: 99%
“…The relatively large energy demands associated with N 2 fixation appear to have largely relegated this process to phototrophic microorganisms found in the well-lit regions of the upper ocean. However, several Gammaproteobacteria and Alphaproteobacteria, as well as several presumed anaerobic bacteria, appear to have the capability of fixing N 2 in the open ocean (Zehr et al 1998;Braun et al 1999;Church et al 2005), although the potential importance of heterotrophic N 2 fixation remains unknown.…”
Section: Nitrogenmentioning
confidence: 99%